Management of Intrapartum Midwifery Care Mrs "E" with Level II Perineal Rupture at UPT BLUD Puskesmas Watampone, Bone Regency: Management of Intrapartum Midwifery Care Mrs "E" with Level II Perineal Rupture at UPT BLUD Puskesmas Watampone, Bone Regency - Muchtar, Asrianti Safitri; Trisna Handayani; Ita Novianti (Jurnal Midwifery, 2023)
Introduction Perineal rupture is a tear in the birth canal spontaneously, perineal rupture is also the second order in the occurrence of Maternal Mortality Rate (MMR) in Indonesia. The main factors that influence the incidence of perineal rupture are primigravida mothers who give birth to newborns weighing > 3500 g, fetal head size > 35 cm, shoulder dystocia, maternal position, and an episiotomy that is intentionally performed using a tool. The importance of providing proper care and the high level of cases of perineal rupture level II, so the purpose of this research was to provide intrapartum midwifery care with level II perineal rupture at UPT BLUD Puskesmas Watampone in accordance with the needs and authority of midwives. Method This study used Varney’s 7-step midwifery care management method and SOAP. Result Based on the case studies that have been carried out, it shows that stage I, stage II, stage II, stage III, stage IV proceeded normally and well, the baby was born normally in good condition, the perineal rupture was resolved and there was no bleeding. Conclusion Case studies by conducting studies in the form of anamnesis and monitoring of intrapartum mothers with level II perineal rupture at the UPT BLUD Watampone Health Center have been assessed, analyzed, and documented regarding all the actions that have been carried out with the results not finding any gaps between the theory and the cases obtained.